15-Lipoxygenase inhibitors: a patent review. (2nd January 2016) - Sadeghian, Hamid; Jabbari, Atena
Abstract : Introduction : 15-Lipoxygenases (15-LOXes) are a family of iron-containing proteins that have the capability for unsaturated fatty acid peroxidation in animals and plants. Two types of the enzyme, 15-LOX-1 and 15-LOX-2, have been recognized in mammals to have different abilities in the peroxidation of arachidonic acid and linoleic acid. In mammalians, the critical role of the mentioned enzymes and their metabolites, hydroxyoctadecadienoic acid (HODE), lipoxins and eoxins, in the formation of inflammation, sensitivities, atherosclerosis and some cancers has been demonstrated. Areas covered : This article reviews relevant publications and patents on 15-LOX inhibitors from the points of view of synthesis and biological activities. Herein, based on the chemical structure and pharmacophore moiety, 15-LOX inhibitors are categorized into heterocyclic, phenolic, allyl and allyloxy derivatives. Expert opinion : It is noteworthy that to date no pharmaceutical product from 15-LOX inhibitors has been approved for therapeutic usage. Recently, the role of 15-LOX-1 in obesity, by directly relating 15-LOX-1 expression with the proliferation and hypertrophy of adipose cells, has been reported. Based on the role 15-LOX plays in promoting cancer by amplifying PPARγ transcription activity, however, it can be claimed that 15-LOX inhibitors will be deemed suitable as chemotherapy agents in the near future.